HUBUNGAN PARITAS IBU BERSALIN DENGAN KEJADIAN KEHAMILAN SEROTINUS DI RSUD Dr.ACHMAD MOCHTAR BUKITTINGGI TAHUN 2014-2015 - Gusmiati, Rita (Jurnal Kesehatan - STIKes Prima Nusantara, 2018)
Community Lead Total Sanitation is a strategy to degrade the incidence of communicable diseases based on the environment and to improve hygiene behavior and quality of life of the community with five pillars of stopping to defecate anyway, handwashing with soap, managing drinking water, and safe food, managing waste and wastewater households properly. This research aims to know the description of knowledge, attitude, and role of health officer in the achievement of five pillars of community lead total sanitation in District of Patamuan. The research design used descriptive method implemented from February to November 2016. The research population was the whole household with sample size 102 RT. Sampling technique by Proportional Random Sampling. Univariate data analysis. Quantitative research results show that most respondents have not reached five pillars of STBM (68.6%), less than half of respondents (45.1%) have low knowledge of sanitation, more than half of respondents (51%) are negative towards sanitation, and more than half of respondents (52%) said health workers had little role to play in sanitation. It can be concluded that the knowledge, attitude, and role of officers are still low in achieving the five pillars of community lead total sanitation. It is recommended to the Puskesmas and District Facilitators to increase extension and empowerment activities to community groups such as triggers so that communities are encouraged not to waste water and build latrine facilities from their own needs and provide training/training to the CLTS committees that have been established to improve the capacity for monitoring activities.